The Effect of Acceptance and Commitment Therapy (ACT) on Post Traumatic Stress Disorder (PTSD) in Adolescents, Post-Flood - Kusno Ferianto; Mei Widyawati (Aloha International Journal of Health Advancement (AIJHA), 2019)
Indonesia is a disaster-prone area, not only natural disasters but also non-natural disasters and social disasters. A disaster event will be a traumatic event for individuals who experience or witness it. One form of psychological impact that is often encountered in flood victims, especially teenagers, is Post Traumatic Stress Disorder (PTSD). PTSD in adolescents can be minimized by giving Acceptance and Commitment Therapy (ACT). This therapy is a behavioral therapy used to reduce avoidance behavior or escape from thoughts, emotions, and memories about traumatic events. The purpose of this study was to determine the effect of ACT on PTSD in post-flood adolescents in Kebomlati Village, Plumpang, Tuban. The research design was a one-group pre-post test design. The sample was selected by simple random sampling. From 150 teenagers, 30 teenagers were taken as respondents. Respondents were given ACT intervention for 6 days. Measurements were carried out using a PTSD screening questionnaire. The data that has been collected was then analyzed using the Wilcoxon test. The results showed that there was an effect of ACT on PTSD in adolescents with a p value of 0.000; so it is concluded that ACT can reduce PTSD. Keywords: Acceptance and Commitment Therapy (ACT); Post Traumatic Stress Disorder (PTSD); flood; teenager